1
$\begingroup$

I found a condition for flat module is projective

" Let $R\subset S$ be an extension of rings. Let $M$ be a flat left $R$-module. For $M$ be projective, it is necessary and sufficient that there exists an exact sequence $$0\to K\to P\to M\to 0$$ of left $R$-module with $P$ projective and the scalar extension $S\otimes_R K$ a finitely generated left $S$-module."

Proof

The necessity is obvious. We prove sufficiency of the conditions stated. Let $Q$ be a projective $R$-module such that $P\oplus Q$ is free. Then with obivious maps, $0\to K\to P\oplus Q\to M\oplus Q\to 0$ is still an exact sequence; also $M\oplus Q$ is a flat module. If we can show that $M\oplus Q$ is projective, it means in particular that $M$ itself is projective. Hence without loss of generality, we can assume that there exists an exact sequence $0\to K\to F\to M\to 0$ of lefft $R$-modules with $F$ free and $S\otimes_R K$, a finitely generated $S$-module. We can also assume that $K$ is a submodule of $F$ and $M$ is the quotient module $F/K$.

Let $\alpha_1,\alpha_2,\dots,\alpha_n$ be a (finite) set of generators of the left $S$-module $S\otimes_R K$. The $\alpha_1$ has the form $$\alpha_1=a_{i_1}\otimes x_{i_1}+ a_{i_2}\otimes x_{i_2}+\dots+a_{i_p}\otimes x_{i_p} $$ where $a_{i_j}\in S, x_{i_j}\in K$ forall $i,j$. Now $\{x_{i_j}\}, i=\overline{1,n},j=\overline{1,p}$ being a finite subset of $K$, the flatness of $M$ ensure the existence of a $R$-linear homomorphism $u:F\to K$ such that $u(x_{i_j})=x_{i_j}$ forall $i,j$. We claim that $u(x)=x$ forall $x\in K$; this mean $u$ splits the inclusions $K\to F$ and hence $M$ will be projective.

By the finiteness of $S\otimes_R K$ as $S$-module, there are elements $\lambda_1,\lambda_2,\dots,\lambda_n$ in $S$ such that $1\otimes x=\lambda_1\theta_1+\lambda_2\theta_2+\dots+\lambda_n\theta_n$. Let $I_s$ denote the identity endomorphism of $S$ onto itself. Then $$ (I_s\otimes u)(\theta_i)=\displaystyle \sum\limits_{1 \le j \le p} {{a_{ij}} \otimes u\left( {{x_{ij}}} \right)} =\sum\limits_{1 \le j \le p} {{a_{ij}} \otimes x_{ij} }=\theta_i$$ This holds for $1\le i\le n$. Hence, $$ \displaystyle \begin{array}{*{20}{l}} {1 \otimes u\left( x \right)}&{ = \left( {{I_s} \otimes u} \right)\left( {1 \otimes x} \right)}&{ = \left( {{I_s} \otimes u} \right)\left( {{\lambda _1}{\theta _1} + {\lambda _2}{\theta _2} + \ldots + {\lambda _n}{\theta _n}} \right)}\\ {}&{}&{ = \displaystyle\sum\limits_{1 \le i \le n} {{\lambda _i}\left( {{I_s} \otimes u} \right)\left( {{\theta _i}} \right)} }\\ {}&{}&{ =\displaystyle \sum\limits_{1 \le i \le n} {{\lambda _i}{\theta _i} = 1 \otimes x} } \end{array}$$ by what precedes. From this $u(x)=x$ will follow if we can show that the canonical homomorphism $K\to S\otimes_R K$ is injective. But this is clear since the canonical homomorphism $F\to S\otimes_R F$ is injective (F being free) and the square $\require{AMScd}$ \begin{CD} 0@> >>K @> >> F\\ @. @VVV @VVV \\ @. S\otimes_RK @>>>S\otimes_R F\\ \end{CD} is commutative. This completes the proof.

Why "$u$ splits the inclusions $K\to F$ and hence $M$ will be projective" and What is the purpose of the proof after "$M$ wil be projective"? Thanks alots!

$\endgroup$
1
$\begingroup$
  1. "$u$ splits the inclusion $K\to F$ and hence $M$ will be projective" means that $u$ will realise $K$ as a quotient of $F$, and the kernel of $u$ will be isomorphic to $M$. Indeed, $u(x)=x$ for all $x\in K$ implies that the kernel of $u$ intersects $K$ trivially, hence injects into $M$ under the projection map $F\to M$; and given any $m\in M$, take any preimage $f$ in $F$, and note that $f-u(f)$ is in the kernel of $u$ (again using that $u(x)=x$ for all $x\in K$) and maps to $m$, so the kernel of $u$ also surjects on $M$. Thus, $M$ would be realised as a submodule of a free module, and it would follow that $M$ is projective.

  2. The rest of the proof is devoted to actually proving the claim that $u(x)=x$ for all $x\in K$.

Your second question is a perfect example of why proofs should be written in linear order; then these kinds of confusions would not arise. Even in that last part of the proof, the author manages to turn the logical order upside down one more time.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.